An Application of Toyota Production System: A case study of Automotive Fuel Tank Manufacturer - หอมศรี ปฐมพงษ์; ไกรฤทธิ์ อัมพิกา; วิสุวรรณ ปรณัฐ (Frontiers in Engineering Innovation Research, 2012)
The main objective of this research is to apply the concept of Toyota Production Systems to improve the automotive fuel tank process in order to eliminating wastes in the manufacturing process and increasing production efficiency, reducing delivery lead time to customer and reducing work space and work-in-process. Many Techniques include standard work, process analysis and production line balancing was implemented to reduce current cycle time to be less than Takt time and to eliminate wastes. The Kanban System was also used to produce parts on time. In addition, improving working area was made to be visually controllable. The results show that increasing the number of tanks assembly process per hour by up to 18.31 %, reducing number of operators by 11.11%, reducing the finished goods inventory by 17.68%, reducing the quantity of work-in-process and lot size by 14.48%. Components and finished goods storage space is reduced by up to 328.81 square meters or 34% and production lead time could be reduced by 86.17% with overall cost saving of factory amounting to approximately 36,008,727.82 Baht per year.